Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/pr9020384
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Choline-Based Deep Eutectic Solvent Pretreatment on the Structure of Cellulose and Lignin in Bagasse

Abstract: Deep eutectic solvents (DESs) is a newly developed green solvent with low cost, easy preparation and regeneration. Because of its excellent solubility and swelling effect in lignocellulose, it has received widespread attention and recognition. In this study, choline-based deep eutectic solvents (DESs)—choline chloride-urea (CC-U), choline chloride-ethylene glycol (CC-EG), choline chloride-glycerol (CC-G), choline chloride-lactic acid (CC-LA), and choline chloride-oxalic acid (CC-OA)—were used to extract and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…As mentioned above, the ability of acidic DESs to depolymerize and fractionate the lignin component of lignocellulosic biomass, as well of hemicellulose, is well known. [67][68][69][70][71] Although a literature comparison of the quantity of extracted biomolecules is of limited value on account of the different biomass sources, extraction protocols, and pretreatment carried out on the waste (for instance brulage or boiling), the here reported MWDA process using DES ChCloxalic acid dihydrate represents an appealing extraction system. This holds true both in terms of yield and TPC as well as for its innovative use of an alternative energy source.…”
Section: Insights Into the Mwda Extraction Mechanism Through The Mw Absorption Response And Heating Behavior Of Chcl-oxalic Acid Dihydratmentioning
confidence: 99%
“…As mentioned above, the ability of acidic DESs to depolymerize and fractionate the lignin component of lignocellulosic biomass, as well of hemicellulose, is well known. [67][68][69][70][71] Although a literature comparison of the quantity of extracted biomolecules is of limited value on account of the different biomass sources, extraction protocols, and pretreatment carried out on the waste (for instance brulage or boiling), the here reported MWDA process using DES ChCloxalic acid dihydrate represents an appealing extraction system. This holds true both in terms of yield and TPC as well as for its innovative use of an alternative energy source.…”
Section: Insights Into the Mwda Extraction Mechanism Through The Mw Absorption Response And Heating Behavior Of Chcl-oxalic Acid Dihydratmentioning
confidence: 99%
“…This makes them interesting for increasing sustainability in chemical technology. Due their capability to form hydrogen bond networks, DES have demonstrated outstanding ability to interact with polysaccharides [ 22 ] and they are being intensely studied as prospective plasticizers for chitosan [ 50 , 51 , 52 , 53 ], starch [ 54 ] and as media for treatment of chitin [ 55 , 56 , 57 ] or cellulose [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. Additionally, using unsaturated acids such as acrylic or methacrylic acids as hydrogen bond donors [ 66 ] provides DES the ability to polymerize in a new green way for preparation of functional materials [ 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…Smink et al (Smink et al 2019) found that the addition of choline chloride in the DES made of lactic acid and choline chloride, accelerates the pulping process, meaning that a higher ber-DES ratio increases the lignin removal. Li et al (Li et al 2021) found that choline chloride as a hydrogen bond acceptor with the urea (hydrogen bond donor) is prone to cleave the lignin-carbohydrate linkages than the breakage of hemicellulose linkages.…”
Section: Discussionmentioning
confidence: 99%